Prenatal diagnosis of pseudomosaicism for trisomy 20 at amniocentesis with a negative non-invasive prenatal testing (NIPT) result in a pregnancy with a favorable outcome - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis of pseudomosaicism for trisomy 20 at amniocentesis with a negative non-invasive prenatal testing (NIPT) result in a pregnancy with a favorable outcome. Case report: A 33-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation, which revealed a karyotype of 47,XX,+20[8]/46,XX[31]. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (1-22,X) × 2, consistent with no genomic imbalance. She was referred to the hospital for repeat amniocentesis at 23 weeks of gestation. At repeat amniocentesis, cultured amniocytes had a karyotype of 47,XX,+20[2]/46,XX[33]. The parental karyotypes were normal. Simultaneous aCGH analysis on the DNA extracted from uncultured amniocytes using SurePrint G3 Unrestricted CGH ISCA v2, 8 × 60 K (Agilent Technologies, Santa Clara, CA, USA) revealed no genomic imbalance, or arr (1-22,X) × 2, Y × 0. Interphase fluorescence in situ hybridization (FISH) analysis using the bacterial artificial chromosome (BAC) probes of RP11-266K16 [20q13.33; fluorescein isothiocyanate (FITC), spectrum green] and RP11-348I14 (20q11.1-q11.21; Texas Red, spectrum red) detected trisomy 20 signals in 4/104 uncultured amniocytes (3.8%), compared with 0/100 in the normal control. Polymorphic DNA marker analysis using the DNA extracted from uncultured amniocytes and parental bloods excluded uniparental disomy 20. NIPT analysis on maternal blood revealed a negative result without gene dosage increase in chromosome 20. The pregnancy was carried to term, and a healthy 2830-g female baby was delivered with no phenotypic abnormality. Both cord blood and placenta had a karyotype of 46,XX. Conclusion: NIPT is useful for rapid differential diagnosis of pseudomosaicism from true mosaicism in case of mosaic trisomy 20 at amniocentesis.